Review Artikel VARIASI PRODUKSI BIOETANOL DARI AMPAS TEBU - Rizki Nurjanah; Martha Aznury (KINETIKA, 2021)
Bioethanol is ethanol made from plants that contain starch, sugar and other cellulosic plants. The general methods used are hydrolysis and anaerobic fermentation methods. This review aims to compare the results of several studies on the manufacture of bioethanol from various raw materials and the treatment of variations in fermentation pH, type of yeast, and fermentation time. Based on the studies that have been carried out, it can be concluded that the largest yield of bioethanol yields is found in research conducted by Guiherme et al. (2019) showing that the yield of bioethanol from bagasse is 88% w / v with. with alkaline pretreatment hydrolysis and anaerobic fermentation methods using the enzymes Kluyveromyces marxianus and Saccharomyces cerevisiae. Then the second largest result was found in research according to Goshandrou et al. (2014) which produced a percent ethanol of 81% v / v from bagasse. with hydrolysis and anaerobic fermentation methods through the Zygomicetes enzyme.